Comparison of psychosocial adjustment in people with diabetes with and without diabetic foot ulceration - (:unkn) unknown (AUSTRALIAN NURSING FEDERATION, 2008)
Objective To determine whether psychosocial adjustment to illness differs in people with diabetes between those who have or do not have diabetic foot ulceration. Design The study employed as a cross-sectional sample survey design. Setting The setting for the study was a training hospital, a marine and undersea medicine outpatient clinic and an endocrinology outpatient clinic. Subjects Two hundred participants with a diagnosis, according to World Health Organization criteria, of type 1 or type 2 diabetes for at least one year were enrolled in the study. 100 participants receiving hyperbaric oxygen therapy had diabetic foot ulceration (DFU) and 100 participants had diabetes without DFU. Outcome measures Data were collected using a demographic data sheet and analysed using the Psychosocial Adjustment to Illness Scale-Self Report (PAIS-SR). Results Advanced age, low education levels, long diabetes duration, poor metabolic control and not exercising may be risk factors for DFU. Total PAIS-SR score was 61.01 +/- 21.42 (poor adjustment) in participants with DFU, and 43 +/- 17.13 (moderate adjustment) in participants without DFU. Participants without DFU had fewer problems in the domain of health care orientation, vocational environment, sexual relationships, social environment and psychological distress than participants with DFU. In participants with DFU; poorer psychosocial adjustment was associated with poorer metabolic control, lower education status, not exercising and retirement. In participants without DFU, women had better psychosocial adjustment than men. Also, participants exercising had better psychosocial adjustment than participants not exercising. Conclusion The participants without DFU had adjusted better to their illness than participants with DFU. The nurse should evaluate and support the patient for psychosocial adjustment to diabetes to prevent chronic complication such as DFU.
Keywords: Type 1 diabetes mellitus; type 2 diabetes mellitus; diabetic foot ulceration; psychosocial adjustment to illness; metabolic control; SELF-MANAGEMENT; METABOLIC-CONTROL; GLYCEMIC CONTROL; THERAPY; RISK; ADAPTATION; DEPRESSION